Peran Pendidikan Islam dalam Mewujudkan Masyarakat Ideal: Perspektif Filsafat dan Transformasi Sosial - Maspuroh, Maspuroh; Irnawati, Wati; Solihin, Wildan; Abdilah Azam, Fikri (LP3M, Universitas Muhammadiyah Kendari, 2025)
The concept of an ideal society in Islam is described in the Qur'an, offering a comprehensive view of the nature of society and the role of education in shaping it. This study aims to examine the concept of society from the perspective of Islamic educational philosophy and understand the role of education in forming an ideal society. Using a qualitative method through a literature review, this study analyzes classical Islamic sources and educational philosophy literature to identify key elements of the ideal society concept. The findings indicate that Islam views society as an organic unity consisting of interconnected individuals with shared goals. Islamic education serves as the primary instrument in shaping individuals' and society's character toward justice, prosperity, and piety. As khairu ummah, Muslims have the responsibility to realize an ideal society through humanization, liberation, and transcendence. In conclusion, the concept of an ideal society in Islam includes ummatan muslimatan, ummatan wasathan, ummatan wahidatan, and khairu ummah, representing a faithful, moderate, united, and exemplary community. This study provides significant contributions to understanding the role of Islamic education in fostering social transformation toward an ideal society.